1993
DOI: 10.1007/bf02399823
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for the existence of cryptic species in theAnopheles albitarsis complex in Brazil: Allozymes and mitochondrial DNA restriction fragment length polymorphisms

Abstract: Allozyme and mitochondrial DNA (mtDNA) restriction studies were undertaken to determine the extent of genetic divergence among field populations of Anopheles albitarsis in Brazil. Two sympatric species, An. deaneorum and An. marajoara, were identified in collections from Costa Marques (CM), Rondonia. Genetic evidence includes (1) the presence of two types of individuals, each with diagnostic allelic clusters (for Had-1, Pgi-1, Pep-1, Mpi-1, and Idh-1), (2) a deficiency of heterozygotes, and (3) characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…Some anophelines were individually tested but most of them were tested in groups of up to 10 selected according to species, location, date and hour of capture. For studies of species complexes, morphological characters, chromosomal 12 and electrophoretic techniques 21 as well as ribosomal 10 and mitochondrial DNA analyses 13 were utilized on both immature and adult anophelines.…”
Section: Methodsmentioning
confidence: 99%
“…Some anophelines were individually tested but most of them were tested in groups of up to 10 selected according to species, location, date and hour of capture. For studies of species complexes, morphological characters, chromosomal 12 and electrophoretic techniques 21 as well as ribosomal 10 and mitochondrial DNA analyses 13 were utilized on both immature and adult anophelines.…”
Section: Methodsmentioning
confidence: 99%
“…Three allopatric populations were detected, with a noteworthy heterozygote deficit and unique haplotypes in each of the populations studied. 12 The second study, using the whole mtCOI gene, 13 found multiple signatures of a demographic expansion event in the eastern Brazilian Amazon. More recently, a third study was done.…”
Section: Introductionmentioning
confidence: 99%
“…The high rate of substitution in mtDNA makes it a powerful tool to address evolutionary questions, especially for those groups which include recently evolved taxa, such as the anopheline mosquitoes. The restriction patterns of mtDNA were used to distinguish the isomorphic species A, B, C and D of the A. dirus complex (Yasothornsrikul et al, 1988), as well as species of the A. quadrimaculatus (Mitchell et al, 1992) and A. albitarsis (Narang et al, 1993) complexes. At the intraspecific level, mtDNA studies have enabled the estimation of intra-and interpopulational variability, sequence divergence, and historical and phylogeographic patterns, as well as the degree of gene flow in A. aquasalis (Conn et al, 1993a), A. quadrimaculatus, A species (Perera et al, 1995), A. darlingi (Freitas-Sibajev et al, 1995;Conn et al, 1999), A. gambiae and A. arabiensis Besansky et al, 1997), A. rangeli and A. trinkae (Conn et al, 1997) and A. nuneztovari .…”
Section: Introductionmentioning
confidence: 99%